Microbial communities from distinct Vitis species shape volatile profiles of fermenting juices while preserving varietal typicity - Raymond Eder, María Laura; Fariña, Laura; Carrau, Francisco; Rosa, Alberto Luis (Frontiers in Fungal Biology, 2025)
Spontaneously fermenting grape juices represent complex ecosystems resulting from the dynamic interaction between the unique characteristics of a grape varietal and its indigenous associated microbiota. The extent to which specific grape variety volatile compounds versus microbially derived ones shape wine identity remains incompletely understood. In this work, we explored this issue by characterizing the volatile compound profiles at early stages of fermentation of the highly aromatic Isabella (V. labrusca L.) grape juice, conducted by native microbial communities prepared from either Isabella (homologous fermentation) or Malbec (V. vinifera L., heterologous fermentation) grapes. Results revealed that microbial starters derived from V. labrusca L. and V. vinifera L. markedly influenced the volatile profiles of the resulting fermented Isabella grape juices. Joint analysis of volatile profiles from Malbec and Isabella juices fermented with the same set of Vitis-specific microbial communities showed that, despite the strong influence of the microbial consortia, the fermented juices retained traits consistent with their original grape varietal identity. Characterization and identification of cultivable yeast species in these homologous and heterologous fermentations of Isabella grape juice showed H. uvarum, H. opuntiae, and S. bacillaris as dominant species in Malbec and Isabella microbial ecosystems. Our results highlight the potential of this innovative experimental approach to examine the relative roles of microbial communities and grape varietals in shaping wine identity. Moreover, they show that different Vitis-specific microbiota can distinctly influence the volatile profiles of a fermenting grape juice without altering its varietal identity.